Effect of maternal employment on exclusive breastfeeding practice among mothers of infants 6-12 months old in Wolkite town, Ethiopia: a comparative cross-sectional study - Amare Zewdie; Temesgen Taye; Abebaw Wasie Kasahun; Abdu Oumer (BMC, 2022)
Abstract Introduction Exclusive breastfeeding (EBF) means providing only breast milk for infants for up to six months without the addition of solid or liquid matter. Even though EBF had great benefits for infants and mothers, the rate of EBF is so limited below the global target. In Ethiopia, the overall EBF practice is 59%. This low EBF practice had a great unexplained variation among employed and unemployed mothers. Therefore, this study aimed to compare EBF practice and associated factors among employed and unemployed mothers of infants aged 6-12 months in Wolkite town, Southern Ethiopia, 2020. Methods A community-based comparative cross-sectional study was conducted in March 2020. A total sample of 485 (241 employed and 244 unemployed) study subjects was involved in the study. A simple random sampling technique was used to recruit study subjects. A pre-tested structured interviewer-administered questionnaire was used. Multivariable logistic regression was used to identify associated factors of EBF practice for the whole study participants and then for employed and unemployed mothers independently. Results The pooled prevalence of exclusive breastfeeding practice was 63.9% [95% CI (59.8-68.2%)]. Exclusive breastfeeding practice was 54.8% [95% CI (48.5-61.4%)] and 73% [95% CI (66.8-78.7%)] among employed and unemployed mothers respectively. Three or more years of a birth interval [AOR = 4.03; 95% CI (1.80-8.99)], three or more ANC visits [AOR = 5.39; 95% CI (1.49-19.45)], and having PNC service [AOR = 4.56; 95% CI (2.0-9.4)] significantly associated to exclusive breastfeeding practice among employed mothers. No history of breastfeeding counseling during ANC visits [AOR = 0.15; 95% CI (0.06-0.41)], had history of breast disease [AOR = 0.28; 95% CI (0.08-0.99)], three or more ANC visits [AOR = 5.11; 95% CI (1.66-15.8)], and having social support [AOR = 3.05; 95% CI (1.23-7.6)] significantly associated to EBF practice among unemployed mothers. Conclusion Employment among mothers was found to discourage EBF practice. The predictors of exclusive breastfeeding practice are different for employed and unemployed. Therefore Policymakers and program planners are called to come together and create a conducive environment for lactating employees, and appropriate intervention at respective predictor variables is needed to enhance EBF practice.